Human and Minority Rights Protection by Multiple Diversity Governance History, Law, Ideology and Politics in European Perspective - Marko, Joseph; Constantin, Sergiu (Taylor & Francis, 2019)
Human and Minority Rights Protection by Multiple Diversity Governance provides a comprehensive overview and critical analysis of minority protection through national constitutional law and international law in Europe. Using a critical theoretical and methodological approach, this textbook: provides a historical analysis of state formation and nation building in Europe with context of religious wars and political revolutions, including the (re-)conceptualisation of basic concepts and terms such as territoriality, sovereignty, state, nation and citizenship; deconstructs all primordial theories of ethnicity and provides a sociologically informed political theory for how to reconcile the functional prerequisites for political unity, legal equality and social cohesion with the preservation of cultural diversity; examines the liberal and nationalist ideological framing of minority protection in liberal-democratic regimes, including the case law of the European Court of Human Rights and the European Court of Justice; analyses the ongoing trend of re-nationalisation in all parts of Europe and the number of legal instruments and mechanisms from voting rights to proportional representation in state bodies, forms of cultural and territorial autonomy and federalism. This textbook will be essential reading for students, scholars and practitioners interested in European politics, human and minority rights, constitutional and international law, governance and nationalism. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license.